A Comparative Understanding of Criminal Liability Formation for Crimes Against Women in Uzbekistan and Cameroon - Suyunova, Dilbar J.; Koniushenko, Yana Yu.; Nguindip, Nana Charles (Ius Humani. Jornal do direito, 2021)
Women continue to be victims of violence and the violation of their human rights keep being in the increase as they experienced constant hatred on their status. This article analyzes liability for crimes against women under criminal legislations of the Republic of Uzbekistan and Cameroon by assessing the Criminal Codes rules in both countries in terms of identifying its distinctive features of legal regulation conditional to gender and family differences of subjects is provided. Expert study of criminal legislations related to crimes against women plays a facilitating role in identifying not only real scope of criminal law rules, but also determining if there is a gap in law, or legal regulation is insufficiently socially conditioned. Moreover, analysis of genesis of criminal standards on responsibility for crimes against women made it possible to trace changes in law in relation to such objects of criminal law protection as, for example, life, health, sexual freedom and sexual immunity, honor and dignity of woman, interests of family and its members.